Protease activated receptor 2 (PAR2) modulators: a patent review (2010–2015). (2nd April 2016) - Yau, Mei-Kwan; Lim, Junxian; Liu, Ligong; Fairlie, David P.
ABSTRACT: Introduction : Protease activated receptor 2 (PAR2) is a self-activated G protein-coupled receptor that has been implicated in several diseases, including inflammatory, gastrointestinal, respiratory, metabolic diseases, cancers and others, making it an important prospective drug target. No known endogenous ligands are available for PAR2, so having potent exogenous agonists and antagonists can be helpful for studying physiological functions of PAR2. Areas covered : This review covers agonist-, antagonist-, antibody- and pepducin-based modulators of PAR2 reported in patent applications between 2010–2015, along with their available structure-activity relationships, biological activities and potential uses for studying PAR2. Expert opinion : In the last six years, substantial efforts were made towards developing PAR2 modulators, but most lack potency or selectivity or have poor pharmacokinetic profiles. Many PAR2 modulators were assessed by measuring Gαq protein-mediated calcium release in cells. This may be insufficient to fully characterize ligand function, since different ligands signal through PAR2 via multiple signaling pathways. It may be feasible to develop biased ligands as drugs that can selectively modulate one or more specific signaling pathways linking PAR2 to a specific diseased state. Accordingly, potent, orally bioavailable, pathway- and receptor-selective PAR2 modulators may be an achievable goal to realizing effective drugs that can treat PAR2-mediated diseases.